2x-4x+3=17

Simple and best practice solution for 2x-4x+3=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4x+3=17 equation:


Simplifying
2x + -4x + 3 = 17

Reorder the terms:
3 + 2x + -4x = 17

Combine like terms: 2x + -4x = -2x
3 + -2x = 17

Solving
3 + -2x = 17

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -2x = 17 + -3

Combine like terms: 3 + -3 = 0
0 + -2x = 17 + -3
-2x = 17 + -3

Combine like terms: 17 + -3 = 14
-2x = 14

Divide each side by '-2'.
x = -7

Simplifying
x = -7

See similar equations:

| 236*3=n | | 2x(4+x)=78 | | y+1=-9(x+3) | | 6m^2+14m+4=0 | | z(x-5x)=210 | | 50=14-4x | | 4x+23=9x-31 | | z(x-5*-5)=210 | | 3y-9whenY=19 | | 7x-5+x-3= | | .20x+.35(50)=27.5 | | y=30+.20x | | 8x(-6)=8 | | y=-x^2+39x-270 | | r+(-4)-2(5)=-16 | | 6+3[15-2(7-3)+1]= | | 16-4x=8x-7x+15 | | 12+8x=y | | 2x^2+24x-72=0 | | 78-2x=90 | | -1(4q+8)+6q=12q-.83(18q+6) | | 4x^3+12x^2-96x+1=0 | | 14+4(x-5)=6+2x | | 3x+2+x=2(2x+1) | | 65=5x+5 | | 2x-4=11+7 | | X^2-498x+4401=0 | | 3x+3(7x+14)=186 | | 3m+5n+7m+6n= | | y=x-8x+7 | | -4.4-2x=0.6 | | 3n+21=-3-2n |

Equations solver categories